Evaluation of the behavior and health anxiety levels the patients applying to the periodontology clinic during the COVID-19 pandemic - Altindal, Dicle; Kaya, Filiz Acun; Yildirim, Tuba Talo; Uysal, Ersin; Duger, Nurullah (Kerman Univ Medical Sciences, 2023)
Objective: The aim of this study was to evaluate the anxiety levels of orthodontic patients during the 1-year period in the ongoing pandemic. Methods: The study included patients between the ages of 12 and 30 years and who were continuing their fixed orthodontic treatment at Ad & imath;yaman University, Faculty of Dentistry, Department of Orthodontics and filled out the State-Trait Anxiety Inventory. A total of 266 patients filled out the questionnaire at their first clinical visit between June 8 and July 8, 2020 (T0) and 176 of 190 patients (response rate: 92.63%) that were still under treatment filled out the questionnaire for a second time between June 15 and July 16, 2021 (T1). Results: In the total population, there was a significant decrease in the State-Trait Anxiety Inventory-S score (P < .05), while there was no significant change in the State-Trait Anxiety Inventory-T score (P > .05). Anxiety scores were significantly higher in women and individuals aged over 18 years at T0 (P < .05), whereas only the anxiety scores of individuals aged over 18 years were significantly higher in T1 than in individuals aged below 18 years (P < .05). The State-Trait Anxiety Inventory-S score showed a significant decrease at T1 compared to T0 for female patients (36.02 +/- 11.32 vs. 38.82 +/- 9.84) and patients aged under 18 years (34.26 +/- 9.54 vs. 36.85 +/- 9.26) (P < .05). Conclusion: The state anxiety levels of orthodontic patients decreased during the 1-year period of the pandemic, while there was no significant change in their trait anxiety levels.
Keywords: Anxiety; COVID-19; Coronavirus; Pandemics